Political education and teaching of social sciences in elementary school (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
The objective of this article is to reflect on the research of the teaching of social sciences in elementary education and political education. At the National University of Comahue we have been conducting didactic research on social knowledge since the second half of the 1990s, all of which were qualitative field research with case studies, conducted in public elementary education institutions in the cities of Neuquén and Cipolletti in North Patagonia Argentina and that seek to contribute to the knowledge of teacher training in social sciences. We present some results of these investigations articulated with the place of participation and political socialization of social sciences teachers and students Interested in knowing about learning in social sciences and the most recent contemporary culture, we will use two articulations that we recognize with explanatory capacity, on the one hand, social knowledge, education and politics and on the other, social knowledge practices that promote an education of feeling-thinking citizenships. The didactics of the social sciences constitute a knowledge of integration, which as such grows and is strengthened to the extent that research is produced in the field that accounts for different perspectives and practices that add different knowledge.
Keywords: research; social sciences; teaching; learning; politics